A Texas Baptist history sourcebook : a companion to McBeth's Texas Baptists - Early, Joseph E. (Joseph Everett), 1970- (University of North Texas Press, 2004)
From the days of Z.N. Morrell and James Huckins to Bill Pinson and Charles Wade, Baptists have played and continue to play an important role in the religious, secular and political life of Texas. This is a collection of Texas Baptist sources.